Evaluation of Bambara Groundnut (Vigna Subterranea (L) Verdc.) Varieties for Adaptation to Rainforest Agroecological Zone of Delta State, Nigeria - E .A, Obidiebube; P .G, Eruotor; S .O, Akparaobi; H, Okolie; C. C, Obasi (International Journal of Sustainable Agricultural Research, 2019)
Field experiments were carried out to evaluate the adaptability of Bambara groundnut (Vigna subterranea (L) Verdc) varieties to rainforest agro-ecological zone of Delta State using selected varieties. The varieties used were: EXMF1, EXMF2, EXMF3, EXMF4, IITA355, IITA182, IITA165, IITA1480, IITA1132, ENZK1 and ENZK2. The aim of this experiment was to identify the varieties of Bambara groundnut that were most suitable in this agro-ecological zone. The design used in this experiment was a Randomized Complete Block Design (RCBD) replicated three times. The parameters collected were: plant height, petiole length, number of leaves, total leaf area, number of pods per plant, pod and seed weights per plant(g), and seed yield (kg/ha). The result showed that varieties EXMF1, EXMF4, IITA165 and ENZK2 performed better than others for growth (plant height, number of leaves and total leaf area) and seed yield. Variety EXMF4 was outstanding in yield with the mean value of 5267kg/ha followed by ENZK2 with the mean value of 5000kg/ha. The least in yield was IITA182 followed by ENZK1 with the values of 2445 and 2600kg/ha respectively.